Status Fosfor Akibat Inokulasi Cendawan Mikoriza Arbuskula dari Berbagai Ordo Tanah di Pertanaman Teh - Faizal Daud (Jurnal Agrista, 2007)
The Status of Phosphour Due To The Inoculation Of Mycorhiza Arbuscula on Various Soil Order On Tea PlantationABSTRACT. To increasing tea crop production and reducing of chemical fertilizer of growth of tea at the same time adjustment of technology of plantation by environmental friendliness of CMA inoculation and usage tea factory waste (fluff) at three tea plantation soil orders. The research aim obtain get CMA which compatible on tea plantation, to knows influence of CMA inoculation and giving compost of fluff to rate nutrient landground, growth and absorption of nutrient and also the improving colonization of CMA at tea crop root. This attempt is arranged Completely Block Design (CBD) of factorial. As first factor was soil orders: which consist of Andisols, Inceptisols and of Entisols. As second factor was CMA inoculation: consist of without inoculation, inoculation with CMA Andisol indigenous, inoculation with CMA inceptisols indigenous, inoculation with CMA Entisol indigenous, inoculation with Glomus fasciculatum, and of inoculation with Gigaspora margarita. While third factor is compost measuring of fluff, without compost, and 20 ton ha-1. From result of third isolation of plantation landground found CMA gender of Glomus sp, inoculation CMA influence rata of nutrient of P, growth of tea crop, absorption of nutrient of P. Indigenous CMA give rate of nutrient P, absorption and growth better of inoculation with CMA non-indigenous. Inoculation Glomus fasciculatum give of rate nutrient of P, growth, and absorption better with inoculation Gigaspora margarita. Giving of compost fluff with 10-15 ton ha-1 real improve rate of nutrient of P, growth of tea and absorption of nutrient P.